2015
DOI: 10.1111/1471-0528.13751
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour change techniques to change the postnatal eating and physical activity behaviours of women who are obese: a qualitative study

Abstract: Objective To explore the experiences of postnatal women who are obese [body mass index (BMI) ≥ 30 kg/m 2 ] in relation to making behaviour changes and use of behaviour change techniques (BCTs).Design Qualitative interview study.Setting Greater Manchester, UK.Population or Sample Women who were 1 year postnatal aged ≥18 years, who had an uncomplicated singleton pregnancy, and an antenatal booking BMI ≥ 30 kg/m 2 .Methods Eighteen semi-structured, audio-recorded interviews were conducted by a research midwife wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This suggests that the BCTTv1 could be a useful tool in identifying active ingredients in lifestyle interventions to promote a reduction in energy intake. This is further supported by qualitative findings where postpartum women identified several strategies including self-monitoring of behaviour as helpful in changing diet and physical activity behaviours [51]. Future postpartum lifestyle interventions should focus on the delivery of effective behavioural strategies, particularly those identified for this group.…”
Section: Interpretation Of Findingsmentioning
confidence: 67%
“…This suggests that the BCTTv1 could be a useful tool in identifying active ingredients in lifestyle interventions to promote a reduction in energy intake. This is further supported by qualitative findings where postpartum women identified several strategies including self-monitoring of behaviour as helpful in changing diet and physical activity behaviours [51]. Future postpartum lifestyle interventions should focus on the delivery of effective behavioural strategies, particularly those identified for this group.…”
Section: Interpretation Of Findingsmentioning
confidence: 67%
“…Hence, recruitment to such interventions requires development of a personal connection with researchers or intervention/class leaders. Research indicates that under study conditions, a dedicated midwife who spends time with women explaining a PA intervention enhances understanding and therefore participation however this may need to be adapted for incorporation into routine antenatal care [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are relatively easy-to-implement behavior change techniques with a one-size-fits-all approach. In contrast, interactive and personalized guidance strategies [e.g., self-monitoring, prompts/cues, social support ( 32 )] were hardly implemented, even though these are considered effective strategies to improve dietary behaviors. To illustrate, Celis-Morales and colleagues ( 33 ) showed that studies using “barrier identification/problem solving,” “plan social support/social change,” “goal setting,” “use of follow-up prompts,” and “provide feedback on performance” were more successful in improving fruit and vegetable consumption compared with studies not using these techniques.…”
Section: Discussionmentioning
confidence: 99%